1987
DOI: 10.1159/000180800
|View full text |Cite
|
Sign up to set email alerts
|

Greater Efficiency of Human Growth Hormone Therapy in Children below Five Years of Age with Growth Hormone Deficiency

Abstract: The effect of human growth hormone (hGH) therapy was studied in 39 prepubertal children with growth hormone deficiency (24 with isolated growth hormone deficiency; 15 with multiple pituitary hormone deficiencies) who had been treated for 2-5 years. They were divided into two groups according to age at the initiation of therapy: group A (n = 21), 0.7-4.8 years (mean chronological age, 2.9 ± 1.4 years, and bone age, 1.2 ± 0.9 years); group B (n = 18), 5.2-9.9 years (mean chronological age, 7.4 ± 1.3 years, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…No significant differences were observed between patients with IGHD or MPD in terms of birth length or characteristics at diagnosis. The analysis of large cohorts of treated GHD patients has revealed several variables influencing outcome (3-6), among them age at onset of treatment (4,5,8,11). In these series, the height gain at final height averages þ0.9 (3) to þ1.7 (11) SDS and compares very unfavorably with our results (þ3.1 SDS at current height).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…No significant differences were observed between patients with IGHD or MPD in terms of birth length or characteristics at diagnosis. The analysis of large cohorts of treated GHD patients has revealed several variables influencing outcome (3-6), among them age at onset of treatment (4,5,8,11). In these series, the height gain at final height averages þ0.9 (3) to þ1.7 (11) SDS and compares very unfavorably with our results (þ3.1 SDS at current height).…”
Section: Discussionsupporting
confidence: 79%
“…Earlier reports have indicated favorable outcomes in GHD patients treated before the age of 5 years. However, the number of patients in these series was often small and the age range at initiation of treatment was broad with a mean of 3 years (8)(9)(10)(11)(12). Two prospective studies (13,14) recently reported early onset of GH treatment (mean 1.5 years of age) in GHD patients, allowing a rapid catch-up growth during the first year of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The study population, however, contained only a minority of children who started treat ment at a very young age. The short-term response in these children is better [4],…”
Section: Discussionmentioning
confidence: 95%
“…Another report, from Josefsberg et al [11] gave the results obtained after 2-5 years of treatment with hGH 2-4 IU 3 times/week, increased to 4-6 IU 3 times/week when the growth rate declined. The authors compared two groups of hypopituitary children: 21 whose treat ment started at age 0.7-4.8 years (14 isolated and 7 mul tiple deficiencies) and 18 whose treatment started be tween 5.2 and 9.9 years (10 isolated and 7 multi-defi cient).…”
Section: Results Of Treatment With Gh In Very Young Hypopituitary Patmentioning
confidence: 97%